OPTIMASI DISTRIBUSI PUPUK MENGGUNAKAN EVOLUTION STRATEGIES - Fauziatul Munawaroh; Wayan Firdaus Mahmudy (Journal of Environmental Engineering and Sustainable Technology, 2015)
The purpose of distribution is accelerating the delivery and equity of goods in various regions. However, the most common problem especially in fertilizer distribution is a high cost distribution in delivery caused by the route and vehicle selection used are less precise and less to maximize the capacity of the vehicle. Several researches have been done using a variety of methods to minimize distribution costs, one of which is the Evolution Strategies algorithm. This research uses permutation representation which is divided into two segments for representate solution. This research using (μ + λ) ES cycle, elitism selection and exchange mutation. Based on this research results, parameters with the best fitness value is the population size of 80, the number of offspring 5, the number of generations of 80, and the composition segments are 30% of segment 1, 20% of segment 2, and 50% for both segments.